Role of influenza A virus NP acetylation on viral growth and replication. Issue 1 (December 2017) - Giese, Sebastian; Ciminski, Kevin; Bolte, Hardin; Moreira, Étori; Lakdawala, Seema; Hu, Zehan; David, Quinnlan; Kolesnikova, Larissa; Götz, Veronika; Zhao, Yongxu; Dengjel, Jörn; Chin, Y. Eugene; et al.
Abstract Lysine acetylation is a post-translational modification known to regulate protein functions. Here we identify several acetylation sites of the influenza A virus nucleoprotein (NP), including the lysine residues K77, K113 and K229. Viral growth of mutant virus encoding K229R, mimicking a non-acetylated NP lysine residue, is severely impaired compared to wildtype or the mutant viruses encoding K77R or K113R. This attenuation is not the result of decreased polymerase activity, altered protein expression or disordered vRNP co-segregation but rather caused by impaired particle release. Interestingly, release deficiency is also observed mimicking constant acetylation at this site (K229Q), whereas virus encoding NP-K113Q could not be generated. However, mimicking NP hyper-acetylation at K77 and K229 severely diminishes viral polymerase activity, while mimicking NP hypo-acetylation at these sites has no effect on viral replication. These results suggest that NP acetylation at K77, K113 and K229 impacts multiple steps in viral replication of influenza A viruses. Post-translational modifications of influenza A virus proteins can regulate virus replication, but the effect of nucleoprotein (NP) acetylation is not known. Here, Giese et al. identify four NP lysine residues that are acetylated in infected cells and study their role in polymerase activity and virion release.